Rethinking the Religious Turn in International Development and Global Governance: A Critical Review of Gerard Clarke - Neirna Yayah Daryati; Mohammad Taufiq Rahman; Asep Abdul Sahid (Jurnal Iman dan Spiritualitas, 2026)
Since the post-World War II era, international development has been dominated by a modernization paradigm grounded in secular rationality, positioning it as a technocratic, growth-oriented project that neglects the religious dimension. However, global dynamics indicate a revitalization of religion in the public sphere (deprivatization), which has triggered a post-secular turn and demands the integration of religious values into development. Religion, in the context of the Global South, has proven to be an important framework for understanding poverty and social practices, as well as a source of legitimacy and moral capital. This article critically examines Gerard Clarke's work "Religion and International Development" using a critical literature review approach that combines theories of secularization, post-secularism, and capability approaches. The findings indicate that religious integration reconfigures understandings of development actors and global governance through the strategic role of faith-based organizations. However, this engagement also carries the risk of exclusion and the politicization of identity. This article argues that the religious turn reflects an epistemological shift toward a post-secular development paradigm, where religion is understood as part of normative negotiations in global governance. Therefore, an inclusive, contextually grounded interdisciplinary approach is needed to manage the relationships among religion, the state, and the market in contemporary global development.